Assessing the structural properties of graphitic and non-graphitic carbons by Raman spectroscopy. (May 2020) - Schuepfer, Dominique B.; Badaczewski, Felix; Guerra-Castro, Juan Manuel; Hofmann, Detlev M.; Heiliger, Christian; Smarsly, Bernd; Klar, Peter J.
Abstract: We study the transformation from molecular to crystalline of (non-)graphitic carbons synthesized from organic precursors by heat-treatment. Easy assessment of structural properties resulting from heat-treatment protocols is mandatory for industrial process monitoring. We demonstrate that Raman spectroscopy, in particular, the Raman lineshape analysis of G and D mode, offers quick assessment of the average sheet size of such carbons. We validate this method by performing Raman, WAXS and EPR measurements of series of resin and pitch-based carbons synthesized. The crystallite sizes of the WAXS analysis for the individual samples are related to corresponding positions and linewidths of G and D Raman modes and show excellent agreement between experiment and modelling from large sizes down to 4 nm. The theoretical master curves are independent of the precursor used in the synthesis, in contrast to models for the intensity ratio of D and G band versus size. We show that the latter are not universally valid and differ for each class of precursors. For sizes below 4 nm, our lineshape model fails as it is based on the bandstructure and phonon dispersions of ideal graphene. Thus, 4 nm corresponds to the fundamental transition from molecular to crystalline character for non-graphitic carbons. Graphical abstract: Image 1